Strategi Pengembangan Usaha Mikro Kecil Dan Menengah (UMKM) Keripik Tempe Selama Masa Pandemi Covid-19 Di Kabupaten Deli Serdang - Siti Wulandari; Mitra Musika Lubis; Ahmad Rizki harahap; Khairul Saleh (Owner : Riset dan Jurnal Akuntansi, 2023)
Tempe chips are food made from soy tempeh in the form of plates / thin slices that are fried with the addition of flour and spices. The problem with tempe chip processing SMEs today is how to develop a strategy for developing micro, small and medium enterprises (UMKM) for tempe chips during the Covid-19 pandemic in Deli Serdang Regency. The purpose of this study was to determine the development strategy of Tempe Chips Micro, Small and Medium Enterprises (MSMEs) during the Covid-19 pandemic in Deli Serdang Regency. The method used to determine the strategy for developing tempeh chips is by using the Analytical Hierarchy Process (AHP) method. Based on the results of research using the Analytical Hierarchy Process (AHP) method of tempe chips in Deli Serdang Regency, a development strategy that is a priority to be applied is by increasing cooperation with retailers so that it will increase consumer purchasing power for tempe chip products. criteria and alternatives that become priority are the value of purchasing power with a weight of 18.16 and the value of retailers with a weight of 35.4. Based on the results of the implementation, the AHP method can provide recommendations in making decisions to increasing purchasing power can be done by increasing cooperation with retailers.